Child Poverty and Its Associated Issues in A City, Tokyo: Insights from Community-Based Participatory Research - Shinpei Ikeda; Yuriko Iwabuchi; Masato Nakamura; Kanta Ohno; Hirotomo Shibahashi (Children)
Background/Objectives: In recent years, despite growing awareness of child poverty in Japan, research examining its impact on the daily lives of children and their families within schools and communities remains limited. This study aims to clarify the extent of child poverty and associated issues in A City, Tokyo, through qualitative research conducted as part of the Community-Based Participatory Research (CBPR) process. Methods: Twelve research participants were selected, including Vice Principals of schools, Community and Child Welfare Officers, and other stakeholders involved in supporting economically disadvantaged households raising children. A focus group discussion (FGD) was conducted on 16 October 2021 to examine the current state of child poverty in A City and local initiatives addressing the issue. Data were analyzed using a qualitative descriptive approach. Results: Three categories emerged from the analysis: (1) Children Disadvantaged by Their Family’s Financial Situation, (2) Challenges in Supporting Financially Struggling Families in Schools and Communities, and (3) the Necessity of Establishing Comprehensive Systems to Support Families. These findings highlight the complex challenges schools and communities face in supporting economically disadvantaged families. Conclusions: Addressing child poverty in A City requires strengthening collaboration between the education sector and community stakeholders, enhancing early detection of poverty-related issues, and establishing comprehensive support systems for timely intervention. However, cultural norms in Japan, such as the reluctance to impose a burden on others, might create barriers to seeking assistance. To overcome these challenges, CBPR is expected to play a key role in fostering networks among children, parents, and support providers.